An analytical study of the performance of public institutions and their role in economic development in Syria during the period 1999-2021 (Journal of Hama University, 2026)
Abstract      This study aimed to analyze the performance of public institutions in Syria and to demonstrate its role in economic development during the period 1999-2021, as this performance was measured by variables close in concept to the concept of gross domestic product, as it is synonymous with the concept of development in economic literature.The data for these variables were taken from the Syrian Statistical Group during the studying period. The data was analyzed using the statistical program E-views 10, and a mathematical model was proposed that controls the relationship between the variables after determining the dependent variable and the independent variables, then ensuring the stability of the chains of those variables and that they are free from a unit root, using The most important statistical tests used in this regard, are the Augmented Dickey-Fuller test and the Durbin-Watson test. The study reached several results the most prominent was:1-There is a large and clear impact of the performance of the public institutions in Syria on the value of the GDP, as the research showed that more than 37% of the changes in the GDP are explained by changes in performance factors, compared to 63% of the changes in the GDP explained by other variables.2- The most prominent variable in its impact on the GDP in Syria is spending on investment in public sector, as the model showed that a one-unit increase in investment spending leads to an increase of 0.899 units in the GDP.
Keywords: key words: GDP - public sector - investment spending - wags spending